Attitude toward and awareness of medical-dental collaboration among medical and dental students in a university in Indonesia - Diah Ayu Maharani; Stacia Ariella; Intan Detrianis Syafaaturrachma; Indriasti Indah Wardhany; Armasastra Bahar; Shinan Zhang; Sherry Shiqian Gao; Chun Hung Chu; Anton Rahardjo (BMC, 2019)
Abstract Background Medical-dental collaboration expands patients' access to health services, improves healthcare outcomes, and reduces the burden and cost of care, especially for those with chronic diseases. The aim of the present study is to investigate the attitude toward and awareness of medical-dental collaboration among medical and dental students attending the Universitas Indonesia. Methods All medical and dental students at the Universitas Indonesia were invited to participate in a web-based questionnaire survey that contained eight questions on attitudes toward medical-dental collaboration and two questions regarding awareness of dental-medical collaborative practices. The demographic backgrounds of all participants were obtained. The chi-square test and logistic regression analysis were employed for data analysis. Results A total of 1,432 questionnaires were distributed, and 1,137 (79%) were appropriately completed. In general, 992 (87%) students had a positive attitude toward medical-dental collaboration. Dental students had a more positive attitude than medical students (odds ratio [OR] = 2.694; p = 0.001), and senior students had a more positive attitude than junior students (OR = 2.271; p = 0.001). Most students (86%) were aware of medical-dental collaboration at the Universitas Indonesia and reported that emergency medicine, surgery, and otolaryngology were the three most common medical disciplines that entailed medical-dental collaboration. Conclusions: In general, the medical and dental students demonstrated positive attitudes and awareness of medical-dental collaboration at the Universitas Indonesia. Positive attitude and awareness can establish an essential foundation for fostering collaboration between medicine and dentistry, which is vital to improve resource efficiency and healthcare standards.